eStroop: Implementation, Standardization, and Systematic Comparison of a New Voice-Key Version of the Traditional Stroop Task - Brunetti, Riccardo; Indraccolo, Allegra; Del Gatto, Claudia; Farina, Benedetto; Imperatori, Claudio; Fontana, Elena; Penso, Jacopo; Ardito, Rita B.; Adenzato, Mauro (Frontiers in Psychology, 2021)
The Stroop effect is a well-documented phenomenon, demonstrating both interference and facilitation effects. Many versions of the Stroop task were created, according to the purposes of its applications, varying in numerous aspects. While many versions are developed to investigate the mechanisms of the effect itself, the Stroop effect is also considered a general measure of attention, inhibitory control, and executive functions. In this paper, we implement “eStroop”: a new digital version based on verbal responses, measuring the main processes involved in the traditional effect. eStroop features four categories of stimuli in four different colors: (1) geometrical shapes, (2) neutral words, (3) congruent words, and (4) incongruent words. The results of the administration to 307 University students confirm the Stroop effect and offer baseline data for future research and clinical testing. Direct comparisons with other recent versions of the task are discussed, offering insights into differences and similarities between different task variables.